Association of the weight status with physical activity: moderation of sociodemographic factors. - Bacil, Eliane Denise Araújo; Piola, Thiago Silva; Pacífico, Ana Beatriz; de Camargo, Edina Maria; Silva, Michael Pereira da; Campos, Wagner de (Children's Health Care)
This study aimed to verify the moderation of sociodemographic factors in the association of weight status with physical activity of 2347 students, both male and female, aged between 11 and 15 years. This study is a cross-sectional correlational descriptive epidemiological survey. We collected body mass measurements, height, gender, age, work, housing, type of residence, parent's education, economic class, and physical activity level. Poisson regression with 95% confidence intervals was used for the association analyses. 33.2% of the students were overweight, and 52.3% were considered active, the highest proportion being boys (64.1%). Overweight girls who do not work (PR = 1,29; CI95% = 1,09–1,53), normal-weight girls who work (PR = 1,83; CI95% = 1,31–2,57), and overweight girls who have a father with ≥ 8 years of education (PR = 1,47; CI95% = 1,14–1,91) were more likely to be active. However, normal-weight girls aged 13 to 15 years were less likely to be active (PR = 0,59; CI95% = 0,48–0,73). We conclude that age, work, and father's education variables influenced the relationship between weight status and adolescents' level of physical activity. Future research needs to understand the relationship between weight status and physical activity and the moderating role of sociodemographic factors to identify the characteristics of Brazilian adolescents and what leads them to be inactive.